Managing for performance : delivering results through others - Jones, Pam, 1960- (Pearson Education, 2009)
Getting your team to perform to the highest possible level is at the core of how well every manager does and is also one of the toughest tasks they have to face. Managers all over the world are struggling to set clear goals and direction for their teams because of a rise in factors including team diversity, different motivations and expectations ...